ANALISIS PENDAMPINGAN PELAKSANAAN COMMUNITY BASE MANAGEMENT (CBM) PADA PROGRAM CORAL REEF REHABILITATION AND MANAGEMENT (COREMAP) DI KAWASAN TAMAN NASINAOL TAKABONERATE SELAYAR - Syamsu Alam Hamid; Abdul Latief (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2015)
This research was conducted in the islands of the National Park neighborhood Takabonerate Selayar, namely in Rajuni Island, Island and Island Tarupa Latondu. Judging from the nature of research is exploratory, namely exploration (exploration) in order to find the right answer and the right of the subject matter of the study. Without the same hypothesis, but rather to establish proposes I -proposisi continuously until missed the entire research problems. Judging from the object of research is sosioogis empirical, that is the main subject of research with empirical facts of sociology on the protection of coastal areas against environmental damage. The data collection is done by in-depth interviews and observations based on the guidelines for the interview (Interview Guide) that had been prepared in advance. The informant is determined intentionally (purposive) against the Companion / Facilitator Fields, leader of the group / retainer and members of fisherman, and his wife and family fishermen recruited as a representation of the 3 islands samples (Rajuni Island, Island and Island Latondu Tarupa).